Milton and the ineffable - Reisner, Noam, 1974- (Oxford English monographs., 2009)
Situating Milton's poetics of ineffability in the context of the intellectual cross-currents of Renaissance humanism and Protestant theology, this text reassesses Milton's poetry in light of the literary and conceptual problems posed by the poet's attempt to put into words that which is unsayable and beyond representation.